2015
DOI: 10.1371/journal.pone.0145001
|View full text |Cite
|
Sign up to set email alerts
|

Community Structure of Arbuscular Mycorrhizal Fungi in Rhizospheric Soil of a Transgenic High-Methionine Soybean and a Near Isogenic Variety

Abstract: The use of transgenic plants in agriculture provides many economic benefits, but it also raises concerns over the potential impact of transgenic plants on the environment. We here examined the impact of transgenic high-methionine soybean ZD91 on the arbuscular mycorrhizal (AM) fungal community structure in rhizosphere soil. Our investigations based on clone libraries were conducted in field trials at four growth stages of the crops each year from 2012 to 2013. A total of 155 operational taxonomic units (OTUs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Each cultivar had four randomized blocks, and soybean was maintained in accordance with the typical agronomic practices in Southwestern China. The rhizosphere soil samples were collected at four growth stages: seedling stage (SS); flowering stage (FS); pod-setting stage (PS) and maturitysetting stage (MS), as previously described (Liang et al 2014(Liang et al , 2015.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each cultivar had four randomized blocks, and soybean was maintained in accordance with the typical agronomic practices in Southwestern China. The rhizosphere soil samples were collected at four growth stages: seedling stage (SS); flowering stage (FS); pod-setting stage (PS) and maturitysetting stage (MS), as previously described (Liang et al 2014(Liang et al , 2015.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies found that the transgenic highmethionine soybean cv. ZD91 had no significant impact on rhizosphere bacterial, arbuscular mycorrhizal fungal community structures and functional diversity of the rhizosphere microorganisms (Liang et al 2014(Liang et al , 2015(Liang et al , 2016. However, the knowledge of the cv.…”
mentioning
confidence: 99%
“…Soybean was maintained in accordance with typical agronomic practices in southwest China. Sampling was carried out at four developmental stages of the plants each year from 2012 to 2013; namely seedling stage (SS); flowering stage (FS); pod-setting stage (PS); maturity-setting stage (MS); as described by Liang et al (2015). Rhizosphere soil samples were collected in accordance with the previous method (Liang et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Transient or no impact of GM plants on the soil microbial community function was found, suggest-ing that there is a potential for adverse transgenic plant-induced impacts on catabolic diversity of microbial communities (Lv et al 2014, Gao et al 2015, Sohn et al 2015. As the safety assessment of GM crops should be case by case (Liang et al 2015), the question arises whether transgenic soybean plants with altered content of methionine will affect soil microbial community catabolic diversity. Although transgenic highmethionine soybean ZD91 was reported to have no significant impact on rhizosphere bacterial and arbuscular mycorrhizal fungal communities structures (Pu et al 2012, Liang et al 2014, knowledge on the effect of GM soybean ZD91 on functional diversity and activity of microbial communities in rhizosphere soil remains fairly limited so far.…”
mentioning
confidence: 99%
“…Andreote, Gumiere and Durrer (2014) pointed for the importance of plant genotype, agricultural practices and phenological stage of plants in determining the composition of microbiomes. The effect of plant growth stages on the rizosphere microbial communities was studied by several authors (Houlden et al, 2008;Cavaglieri, Orlando and Etcheverry, 2009;Hussain et al, 2012;Chaparro, Badri and Vivanco, 2013;Liang et al, 2015;Breidenbach et al, 2016). Liang et al (2015) studied the influence of different soybean varieties on AMF community diversity.…”
Section: Discussionmentioning
confidence: 99%